Los pacientes con trastorno bipolar presentan sesgo emocional en memorias de eventos simuladores de la realidad: Estudio basado en el paradigma de realidad virtual - Bobrowicz-Campos, E.; Maria Salomé Pinho; Matos, A.P. (Revista de Psicopatología y Psicología Clínica, 2016)
This study aimed to examine whether patients with bipolar disorder (BD) perceive differences in the encoding and retrieving of autobiographical information related to events with different emotional valence. For this purpose, an experimental task based on the virtual reality paradigm was administrated to 14 euthymic BD patients and 23 healthy controls. All participants also had a neuropsychological assessment and completed selfreport questionnaires as to mood and psychopathological symptoms. BD patients, when compared to adult controls, recognized more information associated with negative lifelike events and retrieved less information related to positive events. We suggest that changes in processing negative information are caused by the activation of maladaptive emotionregulation processes, and changes in processing positive information arise from insufficient elaboration of memory traces or from suppression/distortion processes acting during retrieval.